Effect of some agronomic technical in morphologe traits, yield compound and oil of rape seed c.v. pactol - Baghdad Science Journal (مجلة بغداد للعلوم)
A field trial was conducted at Abu-Ghraib research station , Baghdad , Iraq . The objectives were to study the effect of nitrogen fertilizer and planting space on the performance of rape seed. A split-plot in a randomized complete of block design with three replications were used. Five levels of nitrogen fertilizer ( 120,160,200,240,280 Kg / ha ) were assigned to main plots, where as planting space in sub-plots. The result obtained confirmed that 280,240 kg / ha nitrogen maximized seed yield 1.830 , 1.773 ton/ha, oil yield,0.843,0.824 ton/ha .Results showed that planting space 30 cm produced the highest seed yield 1.90 ton / ha and oil yield , 0.884 ton / ha . Interactions between nitrogen fertilizer and planting space were also detected plants gave the highest seed yield 2.253 ton / ha and oil yield 1.045 ton /ha that 280kg/ha nitrogen ,30cm planting space and produced more oil content 48.54 % that 120 kg / ha nitrogen compared with high nitrogen fertilizer levels .